Community perception and participation in Silo Laut regarding mangrove management and conservation in Asahan Regency - Rumondang Rumondang; Tri Harsono; Juliwati Putri Batubara; Khairani Laila; Ansoruddin Ansoruddin; Dewi Astuti; Syafrida Br Tambunan; Adelia Fransiska; Zeini Ardianti Putri (Universitas Islam Negeri Sumatera Utara, 2025)
The mangrove ecosystem plays a vital role in maintaining the balance of coastal environments; however, pressures from human activities such as land conversion and overexploitation have led to a decline in its quality and area. This condition necessitates management and conservation efforts that actively involve coastal communities as key stakeholders. This study aims to determine the perception and participation of coastal communities in Silo Laut District, Asahan Regency, regarding the management and conservation of mangrove ecosystems. The research employed a survey method by distributing questionnaires to 276 respondents across three villages: Bangun Sari, Silo Baru, and Lubuk Palas. Data were collected through field observations, structured interviews, and questionnaires containing statements based on the Likert scale. The data were analyzed using the SMART method and Likert scale, and statistically tested with ANOVA analysis. The results showed that most community members have a good perception of the ecological functions of mangrove forests; however, the level of participation and active engagement in conservation activities remains relatively low. The ANOVA analysis revealed that education level, length of residence, and income significantly influence community perception and participation in mangrove ecosystem management, while age and occupation do not show a significant effect. This study provides empirical evidence that community-based socio-economic empowerment programs are a key strategy to support sustainable mangrove conservation in the coastal areas of North Sumatra.